The Effect of Tetraethil OrthoCilicate (TEOS) on Fe3O4 Nanoparticles Addition in Electrical - Indri Dayana; Habib Satria; Martha Rianna (Department of Physics, Sebelas Maret University, 2024)
Magnetite Nanoparticles of pure (Fe3O4) and Fe3O4 with TEOS addition have been successfully synthesized from natural iron sand using the coprecipitation method. The purpose of this study is to provide information on the effect of TEOS to Fe3O4 on the electrical properties. The effect of TEOS addition to Fe3O4 indicates that the increase in true density results is 4.95 gr/cm3. The stability of nanolubricant on Fe3O4 nanoparticles with the addition of TEOS 1.2 ml was dispersed homogeneously. The value of thermal conductivity also increases due to TEOS addition on Fe3O4 nanoparticles in a volume fraction of 0.8% of 1,631 W/m.K and the heat of the type produced was 718.44 J/kg.K. The effect of TEOS addition on Fe3O4 nanoparticles produces good electrical properties of stability in the nano-lubricant.